Characterization and diagnostic work-up of a patient with functionally impaired platelet GP6 - Klümpers, Verena; Schulze, Torsten; Bugert, Peter (Hämostaseologie, 2018)
In this case report of a female patient suffering from a clinically mild bleeding disorder, we describe the complexity of the respective diagnostic work-up to elucidate a suspected functional GP6 defect.